Atomic women : the untold stories of the scientists who helped create the nuclear bomb - Montillo, Roseanne (Little, Brown and Company, 2021)
Documents the lives and careers of the female scientists who worked on the development of the atomic bomb during World War II without recognition or acknowledgement. Discusses how they faced gender discrimination and exclusion, and struggled with the ethics of science and the aftermath of their creation. Includes a scientific timeline, and black-and-white photographs.